Proteomic and metabolomic changes driven by elevating myocardial creatine suggest novel metabolic feedback mechanisms. - Zervou, S; Yin, X; A Nabeebaccus, A; O'Brien, B; L Cross, R; McAndrew, D; Atkinson, R; Eykyn, T; Mayr, M; Neubauer, S; Lygate, C (Springer Verlag, 2016)
Mice over-expressing the creatine transporter have elevated myocardial creatine levels [Cr] and are protected against ischaemia/reperfusion injury via improved energy reserve. However, mice with very high [Cr] develop cardiac hypertrophy and dysfunction. To investigate these contrasting effects, we applied a non-biased hypothesis-generating approach to quantify global protein and metabolite changes in the LV of mice stratified for [Cr] levels: wildtype, moderately elevated, and high [Cr] (65-85; 100-135; 160-250 nmol/mg protein, respectively). Male mice received an echocardiogram at 7 weeks of age with tissue harvested at 8 weeks. RV was used for [Cr] quantification by HPLC to select LV tissue for subsequent analysis. Two-dimensional difference in-gel electrophoresis identified differentially expressed proteins, which were manually picked and trypsin digested for nano-LC-MS/MS. Principal component analysis (PCA) showed efficient group separation (ANOVA P ≤ 0.05) and peptide sequences were identified by mouse database (UniProt 201203) using Mascot. A total of 27 unique proteins were found to be differentially expressed between normal and high [Cr], with proteins showing [Cr]-dependent differential expression, chosen for confirmation, e.g. α-crystallin B, a heat shock protein implicated in cardio-protection and myozenin-2, which could contribute to the hypertrophic phenotype. Nuclear magnetic resonance (¹H-NMR at 700 MHz) identified multiple strong correlations between [Cr] and key cardiac metabolites. For example, positive correlations with α-glucose (r² = 0.45; P = 0.002), acetyl-carnitine (r² = 0.50; P = 0.001), glutamine (r² = 0.59; P = 0.0002); and negative correlations with taurine (r² = 0.74; P < 0.0001), fumarate (r² = 0.45; P = 0.003), aspartate (r² = 0.59; P = 0.0002), alanine (r² = 0.66; P < 0.0001) and phosphocholine (r² = 0.60; P = 0.0002). These findings suggest wide-ranging and hitherto unexpected adaptations in substrate utilisation and energy metabolism with a general pattern of impaired energy generating pathways in mice with very high creatine levels.